MICRO ALGAE CULTURE FROM RAWA GAMBUT: INTRODUCTION STUDY OF MICRO ALGAE POTENTIAL AS BIO DIESEL RAW MATERIAL - Dewi Jumiarni (Universitas Sultan Ageng Tirtayasa, 2018)
Sustainable production of renewable energy is being a crucial problem, since fuel demand in Indonesia rises annually while the production decreases. Microalgae have been suggested as a potential feedstock for biofuel production. This research was a preliminary study to identified microalgal culture from water of peat swamp, and probe its potential as biodiesel feedstock. Microalgal identification was conducted by morphological observation using microscope, while potential as biodiesel was probed by detection using Nile Red staining and supported by literature study. This research has identified 19 species of microalgae from culture, which were consisting of 16 species were Chlorophyceae and 3 species were Bacillariophyceae. Microalgae that potentially to be developed biodiesel feedstock were Cyclotella atomus, Cyclotella sp, Nitzschia sp, Chlorella sp, Desmodesmus sp, Chlorella ellipsoida and Chlorella vulgaris.